2019
DOI: 10.1186/s12886-019-1265-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for glial cell proliferation after idiopathic macular hole repair with internal limiting membrane flap

Abstract: BackgroundTo study the influencing factors for different healing patterns of patients with idiopathic macular holes (IMH) after vitrectomy surgery performed with the internal limiting membrane (ILM) flap technique.MethodsThis study was a retrospective, consecutive, observational case series study. We recruited 52 IMH patients who underwent vitrectomy with the ILM flap technique. The participants were divided into 2 groups: group A (25 patients), without significant glial cell proliferation in the macular area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
(27 reference statements)
1
18
0
Order By: Relevance
“…We also identified the integrity of ELM correlating with an improvement of BCVA. Consistent with findings in other studies, the reintegration of ELM always preceded the reintegration of the EZ and OS in our study [ 29 , 53 , 54 , 59 61 ]. The I-ILM flap technique helps to restore foveal architecture [ 36 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also identified the integrity of ELM correlating with an improvement of BCVA. Consistent with findings in other studies, the reintegration of ELM always preceded the reintegration of the EZ and OS in our study [ 29 , 53 , 54 , 59 61 ]. The I-ILM flap technique helps to restore foveal architecture [ 36 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Liu et al reported hyperreflective foveal lesions in SD-OCT as a possible indicator for excessive foveal glia cell proliferation. An aberrant active glial proliferation in the macular area is associated with worse VA [ 61 ]. However, in our study, there was no indication for re-gliosis in any patient in the long-term cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed eye examination including slit-lamp examination (BQ 900, HAAG-STREOT AG, Swiss), fundus examination by indirect binocular ophthalmoscopy (SL4 4AA, Keeler, USA), and fovea microstructure examinationed by spectral domain OCT (SD-OCT) (RTVue XR 100-2, Optovue, USA) was performed. Preoperative data included age, sex, symptom duration, right or left eye, BCVA (international visual chart), axial length (AL), refractive status, MLD, height (H), base linear diameter (BD) of the macular hole, and central choroid thickness (CCT) 28 . BCVA assessments, OCT and MAIA examinations were performed 1 week, 1 month and 3 months after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…For the analysis of functional outcomes by the ''cover'' versus ''fill'' technique of inverted flap, for example, in patients with holes greater than 400 um and follow up longer than 12 months, 86% and 58% of eyes had regeneration of the ELM and EZ respectively in the ''cover'' group, while no cases had regeneration of either in the insertion group [97], which supported their finding that the ''cover'' group had better final BCVA. One mechanistic hypothesis to explain how this might work is that excessive gliosis in the macula hole seems to be associated with delayed restoration of ELM and EZ [102], and it is possible that a thin flap covering a macular hole is more conducive to minimizing gliosis than multiple flaps filling the hole.…”
Section: Inverted Ilm Flapmentioning
confidence: 99%